2012 GFPR Launch at IFPRI March 14 2013 - Fan, Shenggen (2013)
Launch of IFPRI’s 2012 Global Food Policy Report with Shenggen Fan, Director General of IFPRI; Mary Bohman, Administrator of the Economic Research Service, US Department of Agriculture; Michael Elliott, President and CEO of ONE; Andrew Steer, President and CEO of World Resources Institute. IFPRI, 14 March 2013